2010
DOI: 10.3233/jad-2010-091228
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine, Diabetes, Cognition, and Dementia

Abstract: Abstract. People with diabetes mellitus are at increased risk of cognitive dysfunction. This review explores the relation between caffeine intake, diabetes, cognition and dementia, focusing on type 2 diabetes (T2DM). Epidemiological studies on caffeine/coffee intake and T2DM risk are reviewed. Next, the impact of T2DM on cognition is addressed. Finally, the potential for caffeine to modulate the risk of cognitive decline in the context of diabetes is explored. The conclusion is that, although epidemiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 96 publications
1
26
0
Order By: Relevance
“…Also, some studies reported that coffee consumption lowers the risk of type 2 diabetes [45,46]. Because insulin may have a role in normal cognitive functioning, and it regulates amyloid precursor protein (APP) and amyloid-β protein, insulin resistance may be associated with the pathophysiology of AD [46]. Besides, caffeine can act against neurodegenerative changes in the brain via positive effects on serum lipids [47,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, some studies reported that coffee consumption lowers the risk of type 2 diabetes [45,46]. Because insulin may have a role in normal cognitive functioning, and it regulates amyloid precursor protein (APP) and amyloid-β protein, insulin resistance may be associated with the pathophysiology of AD [46]. Besides, caffeine can act against neurodegenerative changes in the brain via positive effects on serum lipids [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…A main antioxidant in coffee is phenol chlorogenic acid (an ester of caffeic acid and quinic acid), which could carry neuroprotective properties against cognitive deterioration [44]. Also, some studies reported that coffee consumption lowers the risk of type 2 diabetes [45,46]. Because insulin may have a role in normal cognitive functioning, and it regulates amyloid precursor protein (APP) and amyloid-β protein, insulin resistance may be associated with the pathophysiology of AD [46].…”
Section: Discussionmentioning
confidence: 99%
“…18 In contrast, recent studies have reported health benefits associated with coffee consumption. 19,20 At low doses, caffeine improves hedonic tone and reduces anxiety, while it produces an increase in tense arousal, including anxiety, nervousness, and jitteriness, at high doses. 21 Several studies have found that caffeine can reverse many of the performance-impairing effects of ethanol 22 ; for example, a low dose of caffeine prevented the sleepiness and performance impairment associated with a moderate dose of ethanol.…”
Section: Introductionmentioning
confidence: 99%
“…This although can be applied only to nonelderly people who had previously lost weight and there is also positive dose-response relationship between diabetes risk and weight change [7]. Caffeine/coffee consumption is associated with a decreased risk of diabetes type 2 and possibly also with a decreased dementia risk, although further research is needed [8].…”
Section: Caffeinementioning
confidence: 99%